Digital Media Consumption Trends and Changing Consumer Mindsets: A Case Study of Online Shopping Behavior - Deswita, Dhelza; Farisal, Umar; Purwanto, Eko; Naila, Siti Sarah; Putri, Khinandha Aulia Winarto; Putri, Khinantie Winarto; Kamila, Lola Syahira; Mumtaz, Nazwalia Fairuz; Pratiwi, Erida Eka (Indonesian Journal Publisher, 2024)
This study aims to determine the influence of digital media and changes in consumer mindsets in online shopping or e-commerce. E-commerce (electronic commerce) is an activity in the form of buying or selling products electronically on online services or via the internet. E-commerce utilizes technology to introduce goods or services, provide incentives to customers to give and create preferences for product images. This research is a library research using secondary data using indirect methods. The results showed that the main reason for making purchases through e-commerce was due to several things, namely practicality, the absence of products or goods sought directly in the store, many choices and considerations. prices and promotions given in online stores.